The Role of the Village Deliberative Body in Monitoring Village Fund Allocation in the Perspective of Law Number 14 of 2016 - Suramin Suramin; Yasmirah Mandasari Saragih; Ismaidar Ismaidar (International Journal of Law and Society, 2024)
Village funds disbursed by the government sourced from the APBN are still considered as assets that continue to be targeted by certain Village Heads with low morals. The high political costs to get the number one seat in the village cause people to do anything to get it. Because the village funds disbursed are quite tempting. In just one year in mathematical calculations, the capital spent during the process of getting the position of village head can be returned. Therefore, the suboptimal performance of the village head is due to many stumbling blocks of interest. The village head is no longer focused on the promised programs. The village head only focuses on efforts to return the campaign funds spent so far. The high number of corruption cases that hit the village head if it does not become the government's attention, the disbursement of village funds which were originally intended to make the village strong, advanced and independent will be in vain. That is why the role of the Village Consultative Body is needed here, an independent institution whose status is outside the village government. The function of the BPD which is expressly stated in the village law has not been implemented optimally, this results in village fund leaks always occurring every year in almost all regions of Indonesia. This study uses a normative legal research type, namely research that focuses on research on related laws and regulations. The results of this study indicate that Village Fund Supervision in Improving the Performance of the Village Consultative Body has not been guided and based on the principles of Law No. 6 of 2014 concerning Villages. The BPD has not fully carried out its functions. And the obstacles experienced are mainly in the HR aspect besides the absence of regulations that explicitly explain how the technical supervision of the allocation of village funds.